Pengaruh Model Pembelajaran Kooperatif Tipe STAD terhadap Keterampilan Kolaborasi Siswa - Ulfa Luthfiani; Rini Afriani (MASALIQ, 2026)
Although the implementation of cooperative learning models in history learning has been widely studied, discussions that specifically analyze the effectiveness of the Student Teams Achievement Divisions (STAD) model in improving students’ collaboration skills still need to be strengthened. This study aims to analyze the effect of implementing the STAD-type cooperative learning model on students’ collaboration skills in history learning at SMA Negeri 1 Bandar. This study used a quantitative approach with a quasi-experimental design, involving 72 students selected through purposive sampling and divided into experimental and control classes. Data were collected through observation, questionnaires, and documentation, and were then analyzed using simple linear regression tests and t-tests. The results showed that the implementation of the STAD-type cooperative learning model had a positive and significant effect on improving students’ collaboration skills, as reflected in increased communication skills, group responsibility, active participation, and cooperation among students during the history learning process. These findings strengthen the relevance of cooperative learning in supporting the development of 21st-century skills, particularly collaboration skills in the context of history education. The conclusion of this study emphasizes that the STAD model can be used as an innovative student-centered learning strategy to create more active, interactive, and collaborative history learning. The implications of this study provide theoretical contributions to the development of cooperative learning literature and practical implications for teachers and educational institutions in optimizing the STAD model to improve students’ collaboration skills.